استئصال الرحم بالتنظير - عبد الرحمن أحمد (Latakia University Journal -Medical Sciences Series, 2019)
شملت دراستنا (26) مريضة من المرضى المقبولين في مشفى الشاطبي الجامعي التابع لجامعة الإسكندرية في جمهورية مصر العربية وذلك خلال الفترة الممتدة من 9/9/2010 ولغاية 8/1/2011 حيث أجري لهؤلاء المرضى استئصال رحم بالتنظير على الشكل التالي: · (6) استئصال رحم تحت تام بالتنظير · (12) استئصال رحم بالتنظير مع المساعدة مهبليا ً · (8) استئصال الرحم التام بالتنظير أجرينا نصف العمليات(13) حالة باستخدام المخثر ثنائي القطب والنصف الآخر (13) حالة باستخدام التخثير والقطع بالأمواج ما فوق الصوتية. وبحالات استئصال الرحم تحت التام بالتنظير- (6) حالات - استخدمنا لقطع جسم الرحم عن العنق : · العروة / حالتان/ · المخثر ثنائي القطب / حالتان/ · التخثير والقطع بالأمواج ما فوق الصوتية / حالتان / لقد كان أشيع سبب للاستئصال هو الورم الليفي( 61.5% ) . النتيجة : · استخدام العروة أنقص زمن قطع جسم الرحم عن العنق وقلل النزف من سطح القطع . · استخدام التخثير والقطع بالأمواج ما فوق الصوتية أنقص زمن العملية . · استئصال الرحم بالتنظير بمساعدة مهبلية كان أسهل هذه الطرق . · الاختلاطات بشكل عام كانت قليلة وغير هامة . Our study includes 26 patients of the accepted patients at ELSHATBY University Hospital, Alexandria University, Egyptian Arab Republic over the period spanning from 9/9/2010 to 8/1/2011; where they had Laparoscopic Hysterectomy Operations as follows: · 6 cases of Laparoscopic sub – total hysterectomy · 12 cases of Vaginal assisted laparoscopic hysterectomy · 8 cases of Laparoscopic total hysterectomy We have performed half of the operations (13 cases) using Bipolar Coagulation, and the other half (13 cases) using Ultracision Harmonic Scalpel. To cut the uterus body from the cervices in laparoscopic sub–total hysterectomy cases, which are (6 cases), we used: · (two cases) the Loop · Bipolar Coagulation (two cases) · Ultracision Harmonic Scalpel (two cases) The common cause of hysterectomy was myoma (61.5%) Conclusions: · Using cervical loop decreased the time of cutting the uterus body from the cervices and reduced bleeding. · Using Ultracision Harmonic Scalpel decreased the time of operation · Vaginal assisted laparoscopic hysterectomy was the easiest way · Complications were little and insignificant-